INHIBITORY EFFECT OF NON-POLAR AND SEMI-POLAR FRACTIONS OF ETHANOLIC EXTRACT OF Guazuma ulmifolia Lamk. LEAVES ON RAT PREADIPOCYTES PROLIFERATION AND DIFFERENTIATION - Nuri Nuri; Sukardiman Sukardiman; Bambang Prayogo (UPT Penerbitan Universitas Jember)
Jati Belanda Leaves (G. ulmifolia Lamk.) has beenused traditionally to reduce obesity 1). G. ulmifoliaLamk. leaves extract contained alkaloids, tannins,saponins, flavonoids, terpenoids, glycosides, andsteroids 2). Phytochemical screening resultsconducted by Iswantini et al. showed that theflavonoids and tannins were detected high levels inthis extract 3). Flavonoids contained in the leaves ofG. ulmifolia Lamk. were catechin, kaempferolglycosides, procyanidin B-2, procyanidin B-5,procyanidin C-14).Obesity can occur when the body of excess adiposetissue (fat), particularly white adipose. Excess whiteadipose tissue (WAT) is considered as the maincause of obesity 5). The growth of adipose tissueoccurs due to the formation of new adipocytes andincrease in size of adipocytes, called adipogenesis.Adipogenesis involves the multiplication of cells(proliferation) and cell maturation (differentiation).The treatment which can affect the size and numberof adipocytes and signals expression are involved inthe inhibition or stimulation of specific adipokineshave been used to prove the bioactivity associatedwith antiobesity 6).Natural products that have a specific target in thispathway have the potential to prevent and treatobesity. Some polyphenols, including flavonoidshave anti-obesity effects and also specific effects onadipocytes 7). The presence of the flavonoids i.e.catechin, kaempferol, tilirosida, and prosianidin in G.ulmifolia Lamk leaves. may affect adipogenesis.This research will be conducted extraction andfractionation leaves of G. ulmifolia Lamk. Extracts,non-polar fractions and semi-polar fractions testedtheir effect on the proliferation and differentiationof Wistar rat preadiposit.